Reasons for poor academic achievement among public school students in the Qatraneh district in the Karak governorate (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to uncover the causes of poor academic achievement of students inpublic schools in the Qatraneh district in the Karak governorate, and the study sampleconsisted of (408) male and female students, and the study tool included (43) clausesdistributed into three areas (student'sproblems, parent's problems, and school-specificproblems).The results of the study showed that the general level of students 'problems,according to the estimates of the study sample, came at a high or medium level, and thatthe general level of parents' problems came at a high level also for most of the clauses,also, the general level of school-specific problems came at an average level, and theresults showed that there are statistically significant differences for reasons of weaknessand low academic and academic achievement among public school students in theQatraneh district in the Karak governorate for all fields of study according to the gendervariable.The study recommended the necessity of working to address the causes of pooracademic achievement according to the fields of study.